An Examination of the Relationship Among Principals’ Leadership Styles, Principals’ Sense of Efficacy, Teachers’ Sense of Efficacy, Teachers’ Perceptions of Principal Support, and Teachers’ Years of Experience in Urban Georgia Elementary Schools - Sherard, Christina (My University, 2015)
The study, “An Examination of the Relationship Among Principals’ Leadership Styles, Principals’ Sense of Efficacy, Teachers’ Sense of Efficacy, Teachers’ Perceptions of Principal Support, and Teachers’ Years of Experience in Urban Georgia Elementary Schools,” was designed to examine the factors impacting the efficacy of principals and teachers in urban elementary schools as related to different leadership styles, novice and experienced teachers and level of readiness versus leadership style. Based on social learning and motivational theories concerning leadership and efficacy, the theories were significant in identifying characteristics of leadership styles, level of readiness, and the sense of efficacy for principals and teachers. The study utilizes a non-experimental quantitative design employing both a descriptive and inferential analysis. Data were acquired from principals and teachers in two urban school systems in Georgia through the Teacher Sense of Efficacy Scale, Principal Sense of Efficacy Scale, Leadership Styles Questionnaire and the Teacher’s Perception of Principal Support Questionnaire. Of the four research questions posed in this body of research, research question one indicated no significant difference in principal self-efficacy by leadership style. The remaining research questions noted a significant correlation between teachers’ self-efficacy and perceptions of principal support. A statistical significance suggested a difference between the sense of efficacy of principals and teachers as well as a difference in the sense of efficacy of teachers based upon years of experience.
Chapter I: INTRODUCTION 1 Statement of the Problem 3 Purpose of the Study 5 Research Questions 6 Summary of Methodology 7 Conceptual Framework 8 Limitations 10 Delimitations 11 Definitions of Terms 11 Significance of the Study 13 Summary 14 Chapter II: REVIEW OF THE RELATED LITERATURE 22 Introduction to Leadership 25 Modern Leadership Theory 26 Leadership Styles Derived from Leadership Theory 31 Follower Level of Readiness and Leadership Style 34 Leadership Style and Teacher Experience Levels 35 Self-Efficacy Theory 38 Principal Efficacy, Teacher Efficacy and Leadership 39 Summary 42 Chapter III: METHODOLOGY 38 Research Design 39 Research Questions 40 Population 41 Sample 43 Instrumentation 44 Data Collection and Procedures 52 Data Analysis 54 Summary 56 Chapter IV: RESULTS AND INTERPRETATION OF FINDINGS 57 Descriptive Statistics 57 Results for Research Question 1 60 Results for Research Question 2 62 Results for Research Question 3 62 Results for Research Question 4 64 Summary 66 Chapter V: FINDINGS AND CONCLUSION 68 Purpose of Study 68 Summary of Literature 69 Methodology 73 Instrumentation 74 Participants 76 Discussion of Findings 78 Implications for Practice 81 Recommendation for Future Research 82 Conclusion 83 REFERENCES 86 APPENDICES Appendix A: Institutional Review Board Protocol Exemption Report 103 Appendix B: Informed Consent Letter 104 Appendix C: Leadership Styles Questionnaire 105 Appendix D: Principal Sense of Efficacy Scale 107 Appendix E: Teacher Sense of Efficacy Scale 108 Appendix F: Teacher Perceptions of Principal Support 109 Appendix G: Letter of Permission to Use Teacher Sense of Efficacy Scale and Principal Sense of Efficacy Scale 110 Appendix H: Letter of Permission to Use Leadership Styles Questionnaire 111
Keywords: Educational Leadership; Efficacy